Empowerment of MSMEs in the Pastry Sector in Malang City: An Analysis of Policy Implementation - Aryati Aryati; Agus Sholahudin; Roos Widjajani (Trescode Green Organization, 2025)
The purpose of this research is to describe and analyze the implementation of Micro, Small, and Medium Enterprises (MSMEs) empowerment policies in the field of pastries based on East Java Provincial Regulation No. 6/2011 in Purwantoro Village, Blimbing Subdistrict, Malang City, as well as identify supporting and inhibiting factors for its implementation. The research location was Purwantoro Village, Blimbing Subdistrict, Malang City. The data analysis technique in this research used qualitative data analysis based on the results of interviews, observations, and documentation. The findings in the research show that the implementation of MSME empowerment policies in the field of pastries in Purwantoro Village based on East Java Regional Regulation No. 6/2011 has been running, with information dissemination carried out through socialization. However, there are obstacles to access to resources in the form of financial limitations and access to capacity building. In addition, intensive assistance is still needed regarding disposition, especially in marketing, and there is no detailed Standard Operating Procedure (SOP) policy. Supporting factors for implementation include the availability of creative human resources and local government commitment, while the main constraints include limited capital, lack of technical skills, and complex regulations. Capacity building, continuous training, and strengthening business networks are needed to support the sustainability of MSMEs. The research results for the government, especially DISKOPINDAG Malang City, can be used as input in formulating policies related to MSME empowerment.